Pengelolaan Pariwisata di Desa Aursati Kecamatan Tambang Kabupaten Kampar oleh Badan Usaha Milik Desa Permata Sakti - Reren Mei Nelpa Putri; Robi Rendra Tribuana (JYRS: Journal of Youth Research and Studies, 2023)
This research was conducted in Aursati Village, Tambang District, Kampar Regency. The purpose of this research is to find out how the Management of Tourism by Desi-Owned Enterprises in Aursati village and to know the inhibiting factors of Tourism Management by Village-Owned Enterprises in Aursati Village. This type of research is a qualitative descriptive study, research that describes a situation or research conducted to determine the value of an independent variable, either one variable or more without making comparisons or relationships between one variable with another variable. Based on the results of interviews, documentation, and field observations and then analyzed it can be concluded that Tourism Management by the Village-Owned Enterprises (BUMDES) Permata Sakti Aursati Village on development indicators for which sub-indicators are poor supervision due to supervisory institutions that do not implement the SOP, while at the stage institutions and arrangements have been implemented well, and the inhibiting factors are human resources and community participation. .